Which Obstacles Prevent Us from Recruiting into Clinical Trials: A Survey about the Environment for Clinical Studies at a German University Hospital in a Comprehensive Cancer Center - Straube, Christoph; Herschbach, Peter; Combs, Stephanie E. (Frontiers in Oncology, 2017)
Background Prospective clinical studies are the most important tool in modern medicine. The standard in good clinical practice in clinical trials has constantly improved leading to more sophisticated protocols. Moreover, translational questions are increasingly addressed in clinical trials. Such trials must follow elaborate rules and regulations. This is accompanied by a significant increase in documentation issues which require substantial manpower. Furthermore, university-based clinical centers are interested in increasing the amount of patients treated within clinical trials, and this number has evolved to be a key quality criterion. The present study was initiated to elucidate the obstacles that limit clinical scientists in screening and recruiting for clinical trials. Methods A specific questionnaire with 28 questions was developed focusing on all aspects of clinical trial design as well as trial management. This included questions on organizational issues, medical topics as well as potential patients’ preferences and physician’s goals. The questionnaire was established to collect data anonymously on a web-based platform. The survey was conducted within the Klinikum rechts der Isar, Faculty of Medicine, Technical University of Munich; physicians of all levels (Department Chairs, attending physicians, residents, as well as study nurses, and other study-related staff) were addressed. The answers were analyzed using the Survio analyzing tool (http://www.survio.com/de/). Results We collected 42 complete sets of answers; in total 28 physicians, 11 study nurses, and 3 persons with positions in administration answered our survey. The study centers reported to participate in a range of 3–160 clinical trials with a recruitment rate of 1–80%. Main obstacles were determined: 31/42 (74%) complained about limited human resources and 22/42 (52%) reported to have a lack on technical resources, too. 30/42 (71%) consented to the answer, that the documentation effort of clinical trials is too large. A possible increase of the patients’ study participation rate up to over 20% was deemed to be possible if the described limitations could be overcome. Discussion The increasing documentation effort in clinical trials has led to a strong increase in the work load of scientific personnel. Recruiting of patients into clinical trials therefore is not only limited by patient issues, but also by the infrastructure of the centers. Especially the lack of study nurses is likely to be a major limitation. Furthermore, technical resources for time efficient and safe documentation within clinical routine as well as in clinical trials are required. By optimization of these factors, a significant increase in the amount of patients treated in clinical trials seems to be possible.